Strangers on Their Own Land: Examining Community Identity and Social Memory of Relocated Communities in the Area of the Bui Dam in West-Central Ghana - Abrampah, D.A.M. (Human Organization, 2017)
This article examines the importance of social memory among the members of three communities (Bui, Akanyakrom, and Dokokyina) relocated by the construction of the Bui Dam in west-central Ghana. Specifically, the article explores the effects of the resettlement on the affected communities' venerated ancestors, cultural and natural landscapes, as well as the guarding shrines and spirits within the community. The article demonstrates how social memory provides those who are affected by the dam construction an opportunity to renegotiate their social identities, maintain community continuity, and ensure the long-term survival of their cultural history. Based on the research, conducted as part of a broader salvage archaeology project, the article makes several recommendations about how dam authorities can best establish and maintain good working relationships with the affected communities, and also respect their longstanding traditional systems, to ensure successful resettlement and minimal post-relocation livelihood disruptions.
Keywords: Bui Dam; Salvage Archaeology; World Commission on Dams (WCD); Bui Dam Authority (BPA)